Effects on colour discrimination during long term exposure to high altitudes on Mt Everest. Issue 10 (23rd August 2010) - Willmann, Gabriel; Ivanov, Iliya V; Fischer, Manuel D; Lahiri, Sukhamay; Pokharel, Rohit K; Werner, Annette; Khurana, Tejvir S
Abstract : Aim: To investigate changes in colour discrimination as a result of chronic hypoxic exposure induced by extreme altitudes (above 8000 m) during an expedition to Mt Everest. Methods: Colour discrimination thresholds for tritan, protan and deutan axes were measured extensively in two male participants (four eyes) during an expedition to Mt Everest, using a quantitative, computer controlled psychophysical colour vision test (modified version of the Cambridge Colour Test). The tests were carried out over a period of 54 days at altitudes of 1300 m, 3450 m, 4410 m, 5060 m, 5300 m, 6450 m, 7200 m and 8000 m. Results: Colour vision tests 1 week before and 6 months after the expedition indicated normal colour discrimination in both participants. With increasing altitude, colour discrimination thresholds were found to rise, predominantly for the tritan (blue) axes in both observers. Deutan (green) thresholds were minimally elevated at high altitude, whereas protan (red) was altered in one observer. Tritan colour discrimination thresholds decreased as a function of time spent at a given altitude and normalised upon return to low altitude. Conclusions: Chronic hypoxia induced by high altitude exposure transiently affects colour discrimination, in particular tritan axis discrimination. Decreased tritan discrimination is partly reversible upon physiological adaptation to high altitude and completely normalised upon return to low altitude.